Haematological response of common carp Cyprinus carpio to experimental infection with blood stages of the myxozoan parasite Sphaerospora molnari - Tomanová, Anna (Jihočeská univerzita, 2018)
Sphaerospora molnari is a histozoic endoparasite causing severe inflammation during sporeformation in the gills of common carp. As for other myxozoans, little is known about the host response to early proliferation and multiplication of this parasite in the fish host. This thesis is focused on a controlled infection experiment using S. molnari blood stages and on determining cellular and haematological changes of common carp as a response to infection, over a 9-week period post intraperitoneal injection. The results show a noticeable increase in cellular components of innate immunity 14 dpi and a massive increase in lymphocyte numbers, likely B cells, 21-28 dpi. The data are discussed in relation to parasite infection intensity in various tissues and organs, and they strongly point to the acquisition of specific immunity of common carp to S. molnari resulting in a controlled, low level infection from 49 dpi onwards.
Haematological response of common carp Cyprinus carpio to experimental infection with blood stages of the myxozoan parasite Sphaerospora molnari
Keywords: Sphaerospora molnari; carp; myxozoa; haematological response of common carp; Sphaerospora molnari; carp; myxozoa; haematological response of common carp